Pemberdayaan masyarakat lokal melalui inovasi pembuatan pakan pelet di Kampung Toray Papua Selatan - Rizal, Abdul; Praptiwi, Irine Ike; Suriani, Wa Ode; Pramudya, Febri Nur; Yusuf, Mani; Anwar, Anwar; Widiastuti, Maria MD; Sandiah, Natsir (Penamas: Journal of Community Service, 2025)
Toray Village is a border region with significant potential for livestock development, but it still faces challenges in providing sustainable, affordable animal feed. This community service program aims to empower local communities by advancing innovations in the production of animal feed pellets from agricultural and household waste. The activity was carried out through a participatory approach, including training and technical assistance. The results of the activity showed that the community was able to produce economical and nutritious feed pellets, and there was an increase in understanding of waste management as a means to create value-added products. This innovation not only reduced livestock operational costs but also contributed to waste reduction and increased community economic independence. This empowerment model has the potential to be applied in other areas with similar characteristics to support local food security. The implementation method for the activity was counseling and equipment demonstration, covering introduction, operation, management, and maintenance.